Third Five Year Plan A Review - Planning Commission (Planning Commission, 1966)
Kerala's Third Five-Year Plan (1961–1966) aimed to promote balanced regional development through investments in agriculture, industry, infrastructure, and social services, with an outlay of Rs. 170 crores and a target of 5% annual income growth. Key achievements included growth in cash crops, livestock improvement, and industrial modernization, alongside significant road and port infrastructure development. Education expanded through new institutions, technical and medical colleges, and enhanced enrollment, while healthcare facilities and traditional medicine access improved. Social welfare initiatives targeted backward classes and vulnerable populations, complemented by housing schemes, employment services, and community participation. Though some targets were unmet due to climatic and financial constraints, the plan laid a strong foundation for Kerala's economic growth, social development, and institutional capacity building.
Government of Kerala
Government of Kerala
Keywords: Kerala; Third Five-Year Plan; Agriculture; Industry; Education; Health; Housing; Social Welfare; Cooperative Movement; Infrastructure